Physical and chemical characteristics of the Palomero Toluqueño maize race - Bautista Ramírez, Edgardo; Salinas-Moreno, Yolanda; Santracruz-Varela, Amalio; Córdova Téllez, Leobigildo; López-Sánchez, Higinio (Revista Mexicana de Ciencias Agrícolas, 2019)
Accessions of the Palomero Toluqueño maize race do not have information on their capacity for expansion and the physicochemical properties of the grain related to this characteristic. Therefore, the objective of the present was to determine the relationship between the capacity of grain expansion and physical variables (hardness, density, hectoliter weight and thickness of pericarp) and chemical (content of total starch, amylose and amylopectin) in accessions of the Palomero Toluqueño maize race. 18 accessions of this race seven pre-improved materials were evaluated. The materials were cultivated in the spring-summer 2014 agricultural cycle in Montecillo, State of Mexico and Santa María Zacatepec, Puebla. As a witness, a commercial palomero of the brand ‘Valle Verde’ was used. The data of the variables evaluated were analyzed in a completely randomized design, comparison of means and correlation between the variables studied. The average hectolitre weight of the pre-improved materials exceeded by 3.9 kg hL-1 that of the accessions of Palomero Toluqueño. With respect to hardness, the pre-improved materials were statistically similar to the control. The Palomero Toluqueño breed and the pre-improved materials showed pericarp thickness less than 0.6 μm while the control showed 0.9 μm of the control. No statistical difference was observed in the chemical variables evaluated. The hectoliter weight and pericarp thickness were positively correlated with the volume of expansion, which will allow its use as indirect tests in the genetic improvement for the expansion capacity of the Palomero Toluqueño breed.
Keywords: amylose; hardness; hectoliter weight; pericarp; starch